Gestor(a) municipal da saúde no Brasil, sob uma perspectiva regional: perfil, desafios e possibilidades na gestão de temas estratégicos para o SUS - Guedes, Karlla Dannielle da Silva (2023)
Public management practices in the SUS have different expressions and have been conducted by the health managers of the three federated entities. Among these, municipal health secretaries are strategic political actors in defining and shaping the direction of health policy in the country. The responsibilities of these entities were significantly expanded throughout the process of decentralization of social policies, established by the 1988 Constitution, which is an important strategy for social inclusion and democratization of Brazilian society. In this sense, the present study set out to analyze the profile and perception of municipal health managers regarding the strategic challenges linked to the management of the SUS in the Northeast Region. This is a cross-sectional, descriptive and exploratory study with a quantitative approach, with study participants being 141 municipal health secretaries from the Northeast region of Brazil. Data collection took place through two electronic questionnaires, made available via the web to municipal managers, at the beginning of the management cycle (2017) and at the end of the four years in the position of municipal health secretary (2020). The results of the study show that the position of municipal health secretary in the Northeast Region is represented, for the most part, by women, mixed race and black, aged between 30 and 50 years old, with higher education and postgraduate studies, with academic training in nursing and no previous experience in municipal health management. Regarding the perception of the challenges related to Primary Health Care, the managers identified the following as the main difficulties to be overcome: the financial compensation from the state, the implementation of information systems, the need to qualify the teams' work process, in addition to the difficulty of fixing the medical professional at this level of care. Regarding regionalization, strengthening the CIR and regionalization appear as necessities to ensure decentralization and improved access, in addition to expanding financial resources, based on regional differences. Greater participation by the MS and SES in local management practices, associated with the strengthening of SARGSUS, are mentioned as the main challenges to be faced in order to qualify health planning.